In search of the blues - Hamilton, Marybeth (African American music reference., 2008)
Who really invented the Delta blues? A historian debunks the conventional wisdom about an iconic American art form. Leadbelly, Robert Johnson, Charley Patton--we are all familiar with the story of fierce, raw voices, tormented drifters, and deals with the devil at the crossroads at midnight. In this reconstruction of the origins of the Delta blues, historian Marybeth Hamilton demonstrates that the story as we know it is largely a myth. The idea of something called Delta blues only emerged in the mid-twentieth century, the culmination of a longstanding white fascination with the exotic mysteries of Black music. Hamilton shows that the Delta blues was effectively invented by white pilgrims, seekers, and propagandists who headed deep into America's South in search of an authentic Black voice of rage and redemption. In their quest, and in the immense popularity of the music they championed, we confront America's ongoing love affair with racial difference.--From publisher description.